Impact of Ignorance-of-Law in the Criminal Liability from the Perspective of the Islamic Penal Code - Mohammad Hasan Hasani; Seyyed Hosein Shahcheragh (مطالعات فقه و حقوق اسلامی, 2018)
Ignorance-of-law is usually an excuse from criminal liability and among the legal challenges of establishing a balance between maintenance of public order and administration of justice. For the maintenance of social order, everyone is obliged to be aware of the law and the general rule is "ignorance-of-law is no excuse". However, following this maxim would be unfair if proper understanding of the law is impossible. In this regard, the Islamic Penal Code (1392) has adopted a new approach through examining this maxim and its exceptions. Furthermore, some specific rules have been foreseen concerning the ignorance-of-law, especially in the case of punishable offenses and major crimes. This paper aims to explain the general rules and principles of this code and its comparison with the "Dare" Rule, and their limits and credibility in the criminal and non-criminal offences from the perspective of the Islamic Penal Code. Finally, the new approach is criticized.